(untitled) (The Pakistan Development Review, 2018)
The study attempts to investigate the determinants of housing demand in urban areas of Pakistan. The empirical analysis is carried out using the Pakistan Social and Living Standard Measurement (PSLM) survey 2004-05 and 2010-11. The hedonic price model is used for the estimation of house prices. In order to control the selectivity bias between the tenure choice and the quantity of housing services demanded, Heckman’s two-step selection procedure is used. The empirical analysis shows that housing price and income (temporary and permanent) play an important role in the determination of the housing units’ demand. An increase in houses’ prices causes decrease in demand for the housing units while the housing demand increases when the permanent income increases. On the face of change or increase in the transitory income, the demand for housing units remains static, since people do not desire to make long-term decisions based on volatile income. To manage rising housing demand, government should focus on developing effective and enforced price control mechanisms. Keywords: Urban Housing Demand, PSLM, Pakistan